2018
DOI: 10.1187/cbe.18-03-0046
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Research Experience (SRE) in the Traditional Lab: Qualitative and Quantitative Data on Outcomes

Abstract: The San Diego Biodiversity Project introduces undergraduate students at four different 2- and 4-year schools to a short-term research experience (SRE) that was implemented as a module in the last third of a traditional laboratory course. The study assesses the qualities of this SRE for students using three different methods. Twenty-one participants were interviewed about their experiences in the traditional and research components of their course. In a repeated-measures design, 124 participants took the Persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…In the redesigned course, we sought to scaffold scientific skill development and provide increasing opportunities for student-driven inquiry and broadly relevant research throughout the semester. We articulated broad goals for the course and aligned measurable learning objectives that would allow students to engage in authentic research practices and move from peripheral to more central roles in the research community as they acquired skills throughout the semester ( 18 , 19 ) ( Appendix 1 ). A team of laboratory instructors and undergraduate research assistants developed two new course-based research modules (Introductory and Capstone) and modified the existing middle modules during the summer of 2016 (see Appendix 2 for a description of the modules in the redesigned course).…”
Section: Methodsmentioning
confidence: 99%
“…In the redesigned course, we sought to scaffold scientific skill development and provide increasing opportunities for student-driven inquiry and broadly relevant research throughout the semester. We articulated broad goals for the course and aligned measurable learning objectives that would allow students to engage in authentic research practices and move from peripheral to more central roles in the research community as they acquired skills throughout the semester ( 18 , 19 ) ( Appendix 1 ). A team of laboratory instructors and undergraduate research assistants developed two new course-based research modules (Introductory and Capstone) and modified the existing middle modules during the summer of 2016 (see Appendix 2 for a description of the modules in the redesigned course).…”
Section: Methodsmentioning
confidence: 99%
“…The POS measures both cognitive ownership, or the degree to which students feel as though they have intellectual responsibility over their work, and emotional ownership, or the strength of students’ emotions toward their work (Hanauer and Dolan, 2014; Corwin et al , 2018b). Multiple studies have demonstrated that students enrolled in CUREs have high project ownership (Hanauer et al , 2016), and some have found higher levels of project ownership for students who completed a CURE compared with students enrolled in traditional lab courses (Hanauer and Dolan, 2014; Hanauer et al , 2018). However, these studies did not determine what specific aspects of CUREs led to students’ enhanced feelings of ownership and thus were not able to conclude whether students working on broadly relevant novel discoveries enhanced their project ownership.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported the benefits of undergraduate participation in CUREs, including improvements in their research skills, persistence in science, technology, engineering, and mathematics (STEM) fields, and self-regulated learning (Lopatto et al , 2008; Shaffer et al , 2010; Harrison et al , 2011; Rowland et al , 2012; Auchincloss et al , 2014; Jordan et al , 2014; Corwin et al , 2015; Rodenbusch et al , 2016; Hanauer et al , 2018). Increases in students’ content knowledge and project ownership have also been measured after participation in a CURE (Corwin et al , 2015, 2018; Hanauer et al , 2018). Students involved in a CURE course were generally more successful in finding undergraduate research opportunities, including competitive internships (Shaffer et al , 2010; Rowland et al , 2012; Jordan et al , 2014).…”
Section: Introductionmentioning
confidence: 99%